Subjective Factors Influencing Students to Use Bicycle on Campus: A Case Study in Universiti Tun Hussein Onn Malaysia - Ahmad Termida, Nursitihazlin; Zaperi, Noor Haliza; Daniel, Basil David; Endrayana, Dimas Bayu; Hardini, Probo (International Journal of Sustainable Construction Engineering and Technology, 2022)
Malaysia’s energy consumption is predicted to grow over time and the main contributor to the energy consumption is in transport sector.  It is also predicted that energy for transport may expand significantly for the next 25 years.  Therefore, it is vital to create sustainable development in every energy-produced sectors, especially in transport sectors, nationally and globally. One of the measures to reduce energy consumptions in transport sector is to promote sustainable transportation particularly in promoting active transportation mode such as bicycle. This study aims to investigate subjective factors that influence the students’ decisions to use a bicycle for moving on campus.  Probability sampling method using stratified sampling technique was applied since the study was conducted among Universiti Tun Hussein Onn Malaysia postgraduate students.  Survey method via online questionnaire was used and quantitative method in conjunction with relevant statistical approaches such as descriptive statistics and regression analyses was applied to analyse the data.  Theory of Planned Behaviour (TPB) was applied to test the relationships between the factors.  It is found that very few students have used bicycle for movement on campus for participating in mandatory, maintenance and leisure activities in both weekdays and weekends.  Regression results show that subjective factors which are subjective norm, perceived behavioural control, and attitude are strongly influence students’ decisions to use bicycle for daily travels in campus significantly. In addition, the perceived behavioural control that is ease of bicycle use on campus is significantly influenced the behaviour of cycling on campus with similar weightage found with the intention variable.